Incentives and Prosocial Behavior - Roland Bénabou; Jean Tirole (Princeton University, Woodrow Wilson School of Public and International Affairs, 2004)
We build a theory of prosocial behavior that combines heterogeneity in individual altruism and greed with concerns for social reputation or self-respect. The presence of rewards or punishments creates doubt as to the true motive for which good deeds are performed, and this 'overjustification effect' can result in a net crowding out of prosocial behavior by extrinsic incentives. The model also allows us to identify settings that are conducive to multiple social norms of behavior, and those where disclosing one's generosity may backfire. Finally, we analyze the equilibrium contracts offered by sponsors, including the level and confidentiality or publicity of incentives. Sponsor competition may cause rewards to bid down rather than up, and can even reduce social welfare by requiring agents to engage in inefficient sacrifices.
Keywords: D82; H41; D64; Z13; 330; altruism; rewards; motivation; overjustification effect; crowding out; identity; social norms.; Altruismus; Leistungsmotivation; Prestige; Soziale Norm